POLITIK HUKUM PELAKSANAAN KEBIJAKAN VAKSINASI DALAM RANGKA PENANGGULANGAN PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) - Tri Hastuti (Yayasan Merassa Indonesia Publikasi, 2024)
The spread of the Covid-19 virus is taking place all over the world, including in Indonesia Indonesia reported its first case on March 2, 2020 where Presi- dent Jokowi Dodo announced the existence of two cases of Covid-19 positive patients, namely a 31-year-old woman and a 64-year-old mother. 1. How is Indonesia's positive legal arrangement regarding vaccination policies in the era of the Covid-19 pandemic?, 2. How is the implementation of the vaccina- tion policy issued by the government in tackling the covid-19 pandemic? The research approach method used is a doctrinal approach to law. This method emphasizes more on the conception that law can be seen as a set of laws and regulations that are systematically arranged based on a certain order. Indo- nesia as a country affected by the Covid-19 Pandemic responded to the dy- namics of the global pandemic by issuing a citizen vaccination policy that aims to break the chain of spread of Covid-19 in the Indonesia Indonesia, reduce the number of illnesses and deaths due to Covid-19, achieve herd im- munity in the community (herd immunity) and restore economic conditions that had been stalled due to the pandemic. In addition, the implementation of vaccination has also targeted the community, so it is expected to form herd immunity.